Open Source, 3D-Printed TrapGuard to Protect Oil-Sealed Vacuum Pumps from Cold Trap Warming - Spano, Michael B; Pamidi, Arjun S; Weiss, Gregory A (Journal of organic chemistry, 2023)
Clean pump oil is critical to the performance and longevity of oil-sealed vacuum pumps. Cold traps charged with cryogens can protect pump oil from solvent contamination but are subject to operator error. Notably, cold traps with evaporated or warmed cryogens do not protect the vacuum pump. Here, we report an open source device to automatically protect oil-sealed vacuum pumps from cold trap warming and facilitate the daily maintenance of cold traps.